Right to information - Sathe, S P (New Delhi, 2006)
The Right to Information Act 2005 is a legislation passed after years of people's struggle for securing a transparent, accountable and public participatory governance. The passing of this law by Parliament marks a notable milestone in the evolution of the Indian democracy. This book traces the history of this legislation, the evolution of the right to information as a constitutional right and the administrative process involved in the implementation of the above Act. The book represents the endeavor of the Author to present a comprehensive commentary, which is both lucid and analytical. Updated case law and an exhaustive Index facilitate easy reference.
Keywords: Right to information act-2005